Current structure and needs of congenital heart surgery in Europe – a narrative review - Kiraly, Laszlo; Ong, Zhi Xian (Journal of Humanitarian Cardiovascular Medicine, 2025)
Background/Objectives: Congenital heart surgery is a relatively small discipline dealing with a circumscript patient population. The statement contrasts with the discipline’s significant clinical impact for individual patients, and with the public health effect on the healthcare system. The aim of this narrative review is to survey the current landscape of congenital heart surgery in Europe, and especially to revisit the specific points of the recommendation document on the optimal center structure twenty years on. Methods: European demographic patterns and prevalence/incidence of congenital heart disease were studied in national/international information resources. English-language literature of current congenital cardiac surgery practices, outcomes were reviewed. Recommendations on the optimal structure of a pediatric cardiac surgical department were specifically revisited. Results: Europe is an ageing continent with stagnating birthrate. Promoters of congenital heart disease, e.g., consanguinity, segregated generative populations and lack of termination of pregnancy for fetal anomaly are absent. Congenital heart surgery has a long and successful history with world-renown centers of excellence. European professional organizations – joining forces with international counterparts – pioneer cooperation for establishing standards of quality-of-care, risk stratification and international databases. A review of the original recommendations for the optimal center and regional care structure show that statements on volume, quality are still valid; countries with higher socioeconomical index may have an abundance of centers that, in the pursuit of excellence to achieve the best possible outcomes, regionalization is advised. Owing to a much-improved survival, an increased adult population with operated congenital heart disease transits towards the adult services and requests specialized multidisciplinary teams to care for them. Conclusions: Europe enjoys an advanced and accessible healthcare system for congenital heart disease. In fostering development, and focusing on quality-of-life rather than just a mere survival, a concentrated collaborative effort seems essential from the multidisciplinary team, researchers, and policymakers.